Ondansetron, a 5-HT3 antagonist, improves cerebellar tremor. Issue 3 (March 1997) - Rice, G P; Lesaux, J; Vandervoort, P; Macewan, L; Ebers, G C
Abstract : It has been previously shown that ondansetron, a 5-HT3 antagonist, can ameliorate vertigo in patients with acute brainstem disorders. A coincidental benefit was the improvement of cerebellar tremor in some patients with both vertigo and tremor. To further evaluate this effect, a placebo controlled, double blind, crossover study was conducted of a single dose of intravenous ondansetron in 20 patients with cerebellar tremor caused by multiple sclerosis, cerebellar degeneration, or drug toxicity. The principal outcome measures were the change in blind assessment of a writing task (spiral copying) and the timed completion of a nine hole peg test. Thirteen of 19 patients were deemed to have improved spiral copying after treatment with ondansetron when compared with baseline performance. One patient had a better response to the placebo compared with baseline performance (P = 0.00024). Patients completed the nine hole peg test in less time after ondansetron than after placebo (P = 0.08). Twelve patients thought that their tremor was functionally improved with the ondansetron treatment. None thought that the placebo gave improvement (P = 0.00098). The efficacy of orally administered ondansetron in tremor control is currently under study.